Drug‐drug interaction of atazanavir on UGT1A1‐mediated glucuronidation of molidustat in human. Issue 3 (12th December 2020) - van der Mey, Dorina; Gerisch, Michael; Jungmann, Natalia A.; Kaiser, Andreas; Yoshikawa, Kenichi; Schulz, Simone; Radtke, Martin; Lentini, Silvia
Abstract: Molidustat is an oral inhibitor of hypoxia‐inducible factor (HIF) prolyl‐hydroxylase enhancing the erythropoietin (EPO) response to HIF; it is in clinical development for the treatment of anaemia related to chronic kidney disease. The predominant role of glucuronidation for molidustat clearance (formation of N‐glucuronide metabolite M1) and subsequent renal excretion was confirmed in a human mass balance study, with about 85% of the drug being excreted as M1 in urine. The inhibitory effects of 176 drugs and xenobiotics from various compound classes on the UGT‐mediated glucuronidation of molidustat in human liver microsomes (HLMs) were investigated. Based on preclinical findings, glucuronidation of molidustat was predominantly mediated by the 5'‐diphospho‐glucuronosyltransferase (UGT) isoform UGT1A1. Therefore, atazanavir, which is a potent inhibitor of UGT1A1, was chosen for the evaluation of pharmacokinetics and EPO release following a single oral dose of 25 mg molidustat. Molidustat exposure increased about twofold upon coadministration with atazanavir when considering area under plasma concentration‐time curve from zero to infinity (AUC) and maximum plasma concentration ( C max ). Baseline‐corrected increase of EPO was 14% and 34% for C max and AUC (calculated over 24 hours), respectively. Coadministration of molidustat and atazanavir was well tolerated.